2012
DOI: 10.1002/cjoc.201200723
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Mediated Thioetherification of Alcohols with Disulfides or NaSH under Microwave Irradiation

Abstract: An efficient and novel method for the thioetherification of an alcohol with disulfides or NaSH under microwave irradiation is presented. In the presence of iodine, a variety of alcohols were smoothly S-alkylated with disulfides or NaSH to give the corresponding thioethers in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…I 2 was then tested as the catalyst, giving only a low yield of 3aa (23%, entry 2). 12 Further screening of various catalysts showed that Brønsted acids are usually more effective than others (entries 3–8). Among the Brønsted acids tested, the very common, cheap, and easily available bisulfate salts KHSO 4 and NaHSO 4 are the most effective ones for the reaction, with KHSO 4 being the best catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…I 2 was then tested as the catalyst, giving only a low yield of 3aa (23%, entry 2). 12 Further screening of various catalysts showed that Brønsted acids are usually more effective than others (entries 3–8). Among the Brønsted acids tested, the very common, cheap, and easily available bisulfate salts KHSO 4 and NaHSO 4 are the most effective ones for the reaction, with KHSO 4 being the best catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…1 H & 13 C NMR of coupling products are provided in Figures S21–S58. The authors have cited additional references within the Supporting Information [24a,b,31d,32b,c,37,42–43] …”
Section: Supporting Informationmentioning
confidence: 99%
“…Recently, macromolecular β‐nucleating agents have drawn the attention of scientists due to their innocuity, ease of processing and relatively low price. It has been reported that some polymers such as liquid crystal polymer, polystyrene (PS) and acrylonitrile–styrene copolymer (SAN) have β‐nucleating activity and can induce β‐nucleation in iPP . Although there is no general agreement about their β‐nucleation mechanism, it is believed that the benzene rings of these polymers may act as a growth surface for crystals and induce the helix chains of iPP to crystallize epitaxially on it …”
Section: Introductionmentioning
confidence: 99%
“…Improving their β‐nucleating efficiency is a key factor to improving the toughness of iPP. Liquid crystalline polymers have been considered as the most competitive candidates for macromolecular β‐nucleating agents . Hu and colleagues prepared a series of side chain liquid crystal polymers, and the relative content of β‐crystal form ( K β ) was found to be up to 70% .…”
Section: Introductionmentioning
confidence: 99%